Abaloparatide Enhances Fusion and Bone Formation in a Rabbit Spinal Arthrodesis Model. Issue 22 (15th November 2022) - Morse, Kyle W.; Moore, Harold; Kumagai, Hiroshi; Hahn, William; Koo, Alexander; Meyers, Kathleen N.; Bouxsein, Mary L.; Brooks, Daniel J.; Lanske, Beate; Iyer, Sravisht; Cunningham, Matthew
Abstract : Study Design: Prospective randomized placebo controlled animal trial. Objective: Determine the effect of daily subcutaneous abaloparatide injection on the intervertebral fusion rate in rabbits undergoing posterolateral fusion. Study of Background Data: Despite the wide utilization of spine fusion, pseudarthrosis remains prevalent, and results in increased morbidity. Abaloparatide is a novel analog of parathyroid hormone–related peptide (1–34) and has shown efficacy in a rat posterolateral spine fusion model to increase fusion rates. The effect of abaloparatide on the fusion rate in a larger animal model remains unknown. Materials and Methods: A total of 24 skeletally mature New Zealand White male rabbits underwent bilateral posterolateral spine fusion. Following surgery, the rabbits were randomized to receive either saline as control or abaloparatide subcutaneous injection daily. Specimens underwent manual assessment of fusion, radiographic analysis with both x-ray and high-resolution peripheral quantitative computed tomography, and biomechanical assessment. Results: Rabbits that received abaloparatide had a 100% (10/10) fusion rate compared with 45% (5/11) for controls ( P <0.02) as assessed by manual palpation. Radiographic analysis determined an overall mean fusion score of 4.17±1.03 in the abaloparatide group versus 3.39±1.21 for controls ( P <0.001). The abaloparatide group also had a greater volume of bone formed with a bone volume of 1209±543 mm 3 compared with 551±152 mm 3 ( P <0.001) for controls. The abaloparatide group had significantly greater trabecular bone volume fraction and trabecular thickness and lower specific bone surface and connectivity density in the adjacent levels when compared with controls. Abaloparatide treatment did not impact trabecular number or separation. There were no differences in biomechanical testing in flexion, extension, or lateral bending ( P >0.05) between groups. Conclusions: Abaloparatide significantly increased the fusion rate in a rabbit posterolateral fusion model as assessed by manual palpation. In addition, there were marked increases in the radiographic evaluation of fusion.